The Electromechanical Properties of SEBS and SEBS-g-MA Dielectric Elastomer Gels - Kim, Bori; Min, Kyongho; Kim, Jungahn; Hong, Soon Man; Koo, Chong Min (TAYLOR & FRANCIS LTD, 2010)
Electromechanical strain responses of a poly (styrene-b-ethylene-co-butylene-b-styrene) (SEBS) and a maleic anhydride grafted poly (styrene-b-ethylene-co-butylene-b-styrene) (SEBS-g-MA) dielectric elastomer gels have been investigated via an in-situ synchrotron SAXS. The gels had the periodic nanostructures where there was glassy styrene micelles acting as physical crosslink points in the oil swelled rubbery EB matrix. The electromechanical strain of the gel was evaluated from its nanostructure dimension change monitored by the synchrotron SAXS during the electromechanical actuation. The strain was increased with electric field strength. The SEBS-g-MA gel had the higher electromechanical strain response than the SEBS gel at the same electric field.